Automated combined unit with universal tillage adapter - B. Kh. Akhalaya; Yu. S. Tsench; A. V. Mironova (Сельскохозяйственные машины и технологии)
The paper shows that using an automated combined unit with a universal tillage adapter for surface tillage represents a relevant and promising direction in the development of agricultural machinery. (Research purpose) The study aims to develop an automated combined unit equipped with a universal adapter designed to improve soil quality and increase the stability of the unit’s movement. (Materials and methods) The tillage adapter consists of two arc-shaped segments mounted at the front on a common axis that allows rotation. The rear sections contain a mini-hydraulic cylinder, which is remotely connected to the wireless actuator of the unit’s hydraulic system. The arcuate segments are equipped with replaceable cutting attachments and measure 25 centimeters in length. Mounted on a common axis with these segments, a holder is installed at the top at an angle of 40-45 degrees to the horizontal plane, while a saber-shaped slotter is positioned at the bottom at an angle of 15-20 degrees. (Results and discussion) It was discovered that the developed unit, equipped with an innovative adapter, facilitates three simultaneous operations: cutting the soil in a horizontal plane, loosening the soil, and eliminating weeds. Additionally, the working width of the device can be automated adjusted from the tractor cabin. The design of the unit improves tillage quality, increases movement stability, protects segments from wear and reduces manufacturing costs. (Conclusions) The proposed combined soil tillage unit provides crumbling, leveling, rolling and slicing of soil, and improves soil infi ltration. The location of the holder and slotting device with an inclination to the horizontal plane of 40-45 and 15-20 degrees, respectively, reduces the traction resistance of the unit and reduces energy costs.